Clinical epidemiological studies of drug safety and disease risk factors using large primary care databases - Vinogradova, Yana (2017)
BACKGROUND: Observational studies of drug treatments complement pre-marketing drug trials and provide real-world outcomes of effectiveness and safety. Large UK primary care databases offer cost-effective access to clinical information for long-term studies requiring great statistical power and deliver findings representative of the general population. However, such data are not collected primarily for research, so all share weaknesses that must be offset by sophisticated use of statistical methodologies. This paper clarifies the current strengths and limitations of these data sources and discusses their potential. In the context of routinely collected primary care data sources, studies focusing on drug safety are used to show appropriate application of statistical techniques, and present a contribution to existing methodological practice based on multi-database use.